2x+3(2x-9)=(4x+3)

Simple and best practice solution for 2x+3(2x-9)=(4x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(2x-9)=(4x+3) equation:


Simplifying
2x + 3(2x + -9) = (4x + 3)

Reorder the terms:
2x + 3(-9 + 2x) = (4x + 3)
2x + (-9 * 3 + 2x * 3) = (4x + 3)
2x + (-27 + 6x) = (4x + 3)

Reorder the terms:
-27 + 2x + 6x = (4x + 3)

Combine like terms: 2x + 6x = 8x
-27 + 8x = (4x + 3)

Reorder the terms:
-27 + 8x = (3 + 4x)

Remove parenthesis around (3 + 4x)
-27 + 8x = 3 + 4x

Solving
-27 + 8x = 3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-27 + 8x + -4x = 3 + 4x + -4x

Combine like terms: 8x + -4x = 4x
-27 + 4x = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
-27 + 4x = 3 + 0
-27 + 4x = 3

Add '27' to each side of the equation.
-27 + 27 + 4x = 3 + 27

Combine like terms: -27 + 27 = 0
0 + 4x = 3 + 27
4x = 3 + 27

Combine like terms: 3 + 27 = 30
4x = 30

Divide each side by '4'.
x = 7.5

Simplifying
x = 7.5

See similar equations:

| (6x+2)+20=180 | | 5a+6=-8 | | 8x-2x+66=8x+26 | | 2y-4=-10x | | 5y-60332=600y+422 | | -7+2h=-15 | | 2(4b-6)+6(-3-2b)=6-4b+4-5b | | 3x+9=-6x+16 | | 4x+6=y-3 | | 8u+1=7u+1 | | 4k-2=k-6 | | 15+.25x= | | 3(2x+1)=5(x-4) | | 5(b-6)=3(b+4) | | x+y=4x | | 3(3-x)=15x-27 | | -5y+-5(6-2y)=0 | | 15x-10=-9x+3 | | lny=-3ln(x)+ln(C) | | 4-8x-x=-23 | | 3a^2+25a+50=0 | | 8q-5=5q+3 | | 2y+y-.5=23.5 | | 11-9=-23 | | X+6*4=126 | | 8x=4x-6 | | .4x^2+.2=x | | x-6-7=26(x-7) | | -8x-x=99 | | 6n+2=n+8 | | 2(9c-6)=14 | | -4m-2=82 |

Equations solver categories